2011
DOI: 10.1007/s13197-011-0274-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal oxidation of rice bran oil during oven test and microwave heating

Abstract: The purpose of the present study was to evaluate the oxidative stability of physically refined rice bran oil (RBO) under oven heating at 63°C and microwave heating conditions by absorptivity. Oil samples with tertiarybutylhydroquinone (TBHQ) (100 ppm and 200 ppm), citric acid (CA), butylhydroxyanisole/butylhydroxytoluene (BHA/ BHT) and in other combination, BHA/BHT+CA were submitted to oven test for 6 days, and the linear coefficient of correlation between peroxide value and absorptivity at 232 nm was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Hence in the current study, no major hydrolytic degradation was observed with regards to FFA content in both test fats studied. Similar to current study, heating oil itself at 180 did not cause major triacylglycerol hydrolysis 14,22,23,27,33,34 . However, in the presence of food matrix, the acidity values rapidly increased probably due to lipases reaction 6, 35 40 .…”
Section: Resultssupporting
confidence: 88%
“…Hence in the current study, no major hydrolytic degradation was observed with regards to FFA content in both test fats studied. Similar to current study, heating oil itself at 180 did not cause major triacylglycerol hydrolysis 14,22,23,27,33,34 . However, in the presence of food matrix, the acidity values rapidly increased probably due to lipases reaction 6, 35 40 .…”
Section: Resultssupporting
confidence: 88%
“…These species are very unstable and are readily transformed to secondary oxidation products at high temperature, which increases decomposition efficiency. Therefore, PV can be viewed as an indicator of oil oxidative stability [28]. Figure 2 shows the effects of distillation parameters on the peroxide and p-anisidine values of soybean oil.…”
Section: Effect Of Molecular Distillation Parameters On the Extent Ofmentioning
confidence: 99%
“…The changes in PV may be due to the amount of oxygen that must be absorbed or peroxides that must be formed to produce noticeable oxidative rancidity in blended fat which varies with their composition (Mishra et al, 2010). PV of control sample was initially 6.57 for 3:2 blended fat ( Table 1).…”
Section: Effect Of Storage Conditions On Physicochemical Properties Omentioning
confidence: 99%